(untitled) (International journal of artificial intelligence, 2025)
Innovative technologies are significantly changing the modern language learning process, making it more interactive, flexible and personalized. Technologies such as mobile applications, artificial intelligence (AI), virtual reality (VR), speech recognition technologies and online communities provide language learners with modern and effective learning tools. With the help of these technologies, learners can learn a language without the constraints of time and place, compared to traditional learning methods. Technologies also offer innovative methods for mastering the language learning process, for example, allowing learners to create a personal learning path and providing lessons tailored to their needs. At the same time, online communities and language exchange platforms help learners improve their language skills in a natural speaking environment. This article provides a detailed analysis of the role of innovative technologies in the language learning process and their effectiveness.